Metodutveckling för analys av serglycinuttrycket i blodet hos hundar - Sandros, Boel (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2008)
The development of quantitative, real-time PCR (qPCR) combined with the mapping of the canine genome opens new possibilities in veterinary medicine. This method provides a quick and accurate quantification of the expression of a specific gene at a given point in time and thereby also information of how the gene expression for a certain protein is influenced by various conditions and diseases. One possible area of application is identifying bio markers for cancer. Recently the protein serglycin (the core protein of an intracellular proteoglycan) was found to act as a selective marker for the disease acute myeloid leukemia in humans (Niemann et al, 2007). Serglycin is produced by most hematopoietic cells, although mast cells account for the largest amount of serglycin. The expression of serglycin in dogs remains to be explored. As mast cell tumours are common in this species, it would be of interest to find out whether serglycin can be used as a marker for these tumours, to facilitate diagnosis and prognosis as well as evaluation of how well a patient is responding to treatment.